2020
DOI: 10.1088/1742-6596/1617/1/012094
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic Time Series Prediction Using LSTM with CEEMDAN

Abstract: Chaotic systems are complex dynamical systems that play a very important role in the study of the atmosphere, aerospace engineering, finance, etc. To improve the accuracy of chaotic time series prediction, this study proposes a hybrid model CEEMDAN-LSTM which combines Complete Ensemble Empirical Mode Decomposition with Adaptive Noise (CEEMDAN) and long short-term memory (LSTM). In the model, the original time series is decomposed into several intrinsic mode functions (IMFs) and a residual component. To reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The load data sequence of the 5G base station has nonlinear spatiotemporal and other periodic characteristics, so the load data sequence can be regarded as the superposition of various frequency sequences. From the viewpoint of prediction, it can be seen that, when there are fluctuating and periodic characteristics of the sequences with different frequencies, the data sequence has a strong prediction ability [25]. In order to realize the accurate prediction of short-term electricity load data in the past few days, it is firstly necessary to decompose the base station load data sequence according to different frequency characteristics, then construct the load prediction model according to the load sequence of different frequency characteristics, and finally obtain the overall base station load prediction results through the superposition of decomposed sequences.…”
Section: Ceemdan Data Processing Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The load data sequence of the 5G base station has nonlinear spatiotemporal and other periodic characteristics, so the load data sequence can be regarded as the superposition of various frequency sequences. From the viewpoint of prediction, it can be seen that, when there are fluctuating and periodic characteristics of the sequences with different frequencies, the data sequence has a strong prediction ability [25]. In order to realize the accurate prediction of short-term electricity load data in the past few days, it is firstly necessary to decompose the base station load data sequence according to different frequency characteristics, then construct the load prediction model according to the load sequence of different frequency characteristics, and finally obtain the overall base station load prediction results through the superposition of decomposed sequences.…”
Section: Ceemdan Data Processing Frameworkmentioning
confidence: 99%
“…When constructing load prediction models, the introduction of deep learning networks can reveal the load characteristics more essentially. For example, Guo et al combined CEEMDAN with long short-term memory (LSTM) to reduce the difficulty of predicting chaotic time series and improve prediction accuracy [25]. Zou et al combined CEEMDAN, singular spectrum analysis (SSA), and phase space reconstruction (PSR) to achieve higher multilevel prediction accuracy [26].…”
Section: Introductionmentioning
confidence: 99%
“…This chaotic system plays an important role in complex mathematics-based subjects, such as the atmosphere, aerospace engineering, finance, etc. [1] Additionally, research on this complex system in recent years has mainly focused on how to improve the prediction accuracy [1][2][3]. Thus, in this era of big data, scholars are keen to use machine learning and deep learning for predicting stock prices and its trends which is concluded in chaotic system for recent research trends in prediction [4].…”
Section: Introductionmentioning
confidence: 99%
“…Reference [28]also indicated that EEMD can reduce the prediction error. Guo et al [39] proposed hybrid models based on deep learning methods and CEMMDAN have great potential in the field of traffic flow prediction. VMD is the state-of-theart decomposition algorithm, which is seldom employed in the field of short-time traffic flow prediction.…”
Section: Introductionmentioning
confidence: 99%